2017
DOI: 10.1093/eurpub/ckx207
|View full text |Cite
|
Sign up to set email alerts
|

Associations between unemployment and heavy episodic drinking from adolescence to midlife in Sweden and Finland

Abstract: Our results suggest that heavy drinkers are more likely to experience unemployment in subsequent years. The associations from HED to unemployment seem to exist through the life course from adolescence to midlife. More emphasis should be put on reducing alcohol related harms in order to improve labour-market outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 29 publications
1
20
1
Order By: Relevance
“…Based on wave 5 of the Lifelines Cohort Study (gathered between 2016 and 2019), the following drinking patterns were assessed: "Abstinence", "Moderate drinking" and "Heavy or Binge drinking" (including either " > 1.5 glasses/ day on average" or "4 or more drinks/occasion" in the last month [34]).…”
Section: Pre-pandemic Alcohol Consumptionmentioning
confidence: 99%
“…Based on wave 5 of the Lifelines Cohort Study (gathered between 2016 and 2019), the following drinking patterns were assessed: "Abstinence", "Moderate drinking" and "Heavy or Binge drinking" (including either " > 1.5 glasses/ day on average" or "4 or more drinks/occasion" in the last month [34]).…”
Section: Pre-pandemic Alcohol Consumptionmentioning
confidence: 99%
“…Previous studies on risky alcohol intake and alcohol‐related problems have generally, but not consistently, demonstrated a positive association with youth unemployment . However, research has also found evidence for the reverse effect, as well as no effect . Consequently, the relationship between unemployment and alcohol is complex, as risky alcohol intake appears to be both a risk factor and a consequence of unemployment .…”
Section: Introductionmentioning
confidence: 97%
“…The first topic I will address here concerns the direction of causality. This issue has been particularly debated in relation to employment and alcohol consumption [84,85]. Does unemployment lead to alcohol abuse?…”
Section: Methodological Issuesmentioning
confidence: 99%
“…All in all, after decades of academic discussion, there is certain consensus that both causation and selection operate simultaneously, in a bidirectional association [56,84], and the relative importance of one or the other is highly context-dependent [89]. Furthermore, a third causal element has been increasingly considered in recent years: "indirect health selection", i.e., common distal causes (usually early exposures in life, such as childhood deprivation or unmeasured health-or SES-related variables) that may, in turn, affect both health (behaviours) and SES.…”
Section: Causation Vs Selectionmentioning
confidence: 99%
See 1 more Smart Citation